A Brief of Water and Soil Pollution Management (Recent Trend and Economic Perspective) - Muhammad Safri; Nurhayani Nurhayani; Desy Rosarina (Universitas Diponegoro, 2021)
Soil and water pollution are the most crucial issues in the world. Various reports have informed that pollution has had long-term adverse effects on environmental sustainability and human health. Several methods have been reported to be effective in reducing pollutant parameters in water and soil. The methods often used in water and soil remediation are bioremediation (land-vetting, bio-cell. Bio cell, Phytoremediation, Land venting, Composite, Bio venting, Bio slurry), Adsorption, Pretreatment (Ultrasonic), Microwave, Electrokinetic disintegration, High-Pressure Homogenization/HPH, Thermal Hydrolysis, Acid hydrolysis (HCl, H2SO4, H3PO4, and HNO3), Ozonation, Fenton Oxidation, Fe (II) -activated persulfate, Protease, amylase, lipase. This paper will explain water and soil pollution and the methods used to overcome them. Information collection is carried out using secondary data; internationally reputable journals and accredited national journals are used to obtain information about the effectiveness and costs incurred. This paper will provide a holistic comparison of prices, effectiveness, and information on various remediating water and soil pollution methods around the world. Based on the NPV and IRR analysis, the water treatment method using the adsorption method is an economically feasible method with an IRR value of 51%.